PERANAN EKSTRAK KULIT PISANG UNTUK MENGATASI KATARAK DENGAN HEWAN COBA TIKUS (Rattus norvegicus) - Mahmudah, Gustin; AS, Hanindhitya Lintang; F, Fabianus Winant; F, Syifai Triana (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
This study aimed to determine the benefits of banana peel extract to prevent and cure of cataracts. Twenty four rats, 19 days old were divided into eight experimental groups. To develop cataract models, rats were induced by sodium selenites 15 Î¼mol/kg body weight/subcutan (sc). The groups of rats that were induced by sodium selenites and banana peel extract, showed the healing progress of eyes with the thickness of the fog on eyes. The banana peel extract could prevent of cataracts at a concentration of 25% and cure of cataracts at a concentration of 50%.